Environmental degradation, economic growth, and energy consumption: The role of education. (11th January 2023) - Osuntuyi, Busayo Victor; Lean, Hooi Hooi
Abstract: The growth‐energy‐environment relationship has been debated over the last decades. The devastating impacts of economic growth and energy consumption on the environment have concerned environmental stakeholders worldwide. Although education has been identified as an essential determinant of environmental degradation, its moderating role is overlooked in the literature. This study examines the direct and moderating roles of education in the growth‐energy‐environment relationship in 23 African countries. The panel mean group (MG), pooled mean group (PMG), fully modified ordinary least squares (FMOLS) and the Driscoll–Kraay standard errors are used for the analysis. The study finds that the direct and moderating roles of education aggravate environmental degradation. The findings also reveal that the marginal impacts of energy consumption are contingent upon education and increase environmental degradation. The study recommends transforming the school curriculum to foster environmental awareness, competence, and mindset to improve the environment in Africa.